Second self - McCormack, Una (Star trek. Picard., 2022)
"Following the explosive events seen in season one of Star Trek: Picard, Raffi Musiker finds herself torn between returning to her old life as a Starfleet Intelligence officer or something a little more tame--teaching at the Academy, perhaps. The decision is made for her though when a message from an old contact--a Romulan spy--is received, asking for immediate aid. With the help of Elnor and assistance from Jean-Luc Picard, Raffi decides to take on this critical mission--and quickly learns that past sins never stay buried. Finding the truth will be complicated, and deadly..." --